Update on Multiple Myeloma - Ahmed Al-Anazi, Khalid (IntechOpen, 2019)
This book is a comprehensive overview of the recent developments in the clinical and research fields of multiple myeloma. It is divided into three main sections that cover a wide range of topics, including: epidemiology and pathogenesis of the disease, genetic targets and pathways, resistance to novel therapies, angiogenesis and anti-angiogenesis, hematopoietic stem cell transplantation, role of radiology and radiotherapy in myeloma, infectious complications, and management of multiple myeloma in resource-poor countries.